Assessment of sustainable development in the urban poles status of the urban pole Retba (Municipality of Didouche Mourad-Constantine) - Haouari, Souad (Journal of Humanities & Social Sciences, 2023)
Achieving sustainable city development is a goal sought after by many countries— one of which is Algeria. The hope is to strike a balance between economic development needs and social needs, with optimal utilization of ecosystems within geographical spheres, more so after the development of urban poles. This is only achieved through compatibility testing between goals and tangible outcomes. Monitoring measurements through both quantitative and qualitative means, such as the internationally accredited System for Leadership in Energy and Environmental Design (LEED-ND). Bearing this in mind, the paper aims to study the degree of sustainable development of urban poles through a theoretical approach to deciphering relevant concepts, coupled with descriptive analytics analyzing the subject of study, the urban pole of Rutba, located in Didouche Mourad County, in the state of Constantine. The process utilizes indicators of the internationally accredited System for Leadership in Energy and Environmental Design (LEED-ND), in the evaluation of sustainable development, which has shown a tremendous lag in developing these poles, despite continuous efforts.
Keywords: Sustainable development; urban pole; development indicators; Retba area